Evaluasi Program Pelatihan Manajemen Unit Ruang Rawat (Kirkpatrick Level I Dan II) Di RSUD Praya-Nusa Tenggara Barat, 2020 - Lalu Muhammad Harmain Siswanto (Jurnal Kesehatan Qamarul Huda, 2020)
The management of ward unit training aims to make the Head of the Ward more skilled and able to carry out his duties effectively and efficiently, it is necessary to develop himself through appropriate training. Training evaluation activities need to be carried out to determine the success of a training room management unit that has been held. Given that there has never been an evaluation of this training. To find out the results of the evaluation of the facilitators, the implementation and evaluation of the participants' knowledge. This research is a type of quantitative research. Observational descriptive research design. The approach used prospectively. The population for this study were nurse managers. The number of participants in the training of inpatient room management in this study was 30 people. The evaluation was carried out using the KirkPatrick Level 1 and 2 Model namely Reaction (participant evaluation, facilitator and implementation) and Learning (Participant Knowledge). Instruments for Level 1 use the Evaluation Sheet for Facilitators, Implementation, Level 2 using the evaluation sheet for the Pre Post Test questions. The results of this study generally show that the training participants' evaluation of resource persons is in the very good category and the evaluation of the training is good. The knowledge of the training participants before training was 76.7% in sufficient category and after training 90% in good category. The training went well as evidenced by the increase in the training participants' knowledge. Training needs to be held in other hospitals by paying attention to training principles. It needs to be input for further researchers to use qualitative methods or a mix of methods to have a deeper look at the implementation of training.